Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin